Playful interactions and facial mimicry in infant bonobos (Pan paniscus). Issue 3 (4th May 2022) - Bertini, Marta; Annicchiarico, Giulia; Bresciani, Chiara; Cordoni, Giada; Palagi, Elisabetta
Abstract : The capacity to promptly and congruently respond to others' facial signals has at its basis a mirror neuron mechanism. In Rapid (< 1 sec, RFM) and Delayed (1–5 sec, DFM) Facial Mimicry the expression emitted by an individual (trigger) is perceived and replicated by an observer. The occurrence of mimicry phenomena has been demonstrated almost exclusively in the play domain. Here, we aim at evaluating the presence of RFM/DFM during playful interactions between infant bonobos ( Pan paniscus ), one of the most playful primate species. We video-recorded 435 play sessions between five infants (< 48 months of age) belonging to the bonobo colony hosted at the Wilhelma Zoo (Germany). Via a frame-by-frame video-analysis, we demonstrated the presence of both RFM and DFM. These two phenomena were enhanced by face-to-face interactions between playmates. Hence, the access to others' faces allows the player to perceive, decode and replicate signals, thus promoting a mutual intersubjective engagement with the partner. The occurrence of DFM suggests that in bonobos, as in chimpanzees, such mirror event is present just starting from infancy. The less automaticity characterizing DFM compared to RFM could be due to the involvement of more complex and time-demanding cognitive processes. Neither RFM nor DFM increased the duration of play sessions. Probably, the mimicry phenomena in infant bonobos are not recruited for manipulating the sessions, which are highly balanced and fair, but possibly for sharing the playful mood between interacting subjects thus increasing their level of familiarity and affiliation.